2020
DOI: 10.18502/ssu.v27i10.2406
|View full text |Cite
|
Sign up to set email alerts
|

Narration the Lived Experiences of Career Couples of Family Function, Health Dimension

Abstract: Introduction: Family function has been changed by the couple's simultaneous employment and presents particular problems for the family and the couples. One of the dimensions that is strongly influenced by the functioning of the working couple's family is the health dimension. The purpose of this study was to extract living experiences of career couples from the health aspect of family functioning. Methods: This research was done by qualitative approach and by the method of interpretive phenomenology. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Rahimi et al found that the distribution of roles, responsibilities, and power in skilled couples is fair while it is unfair in unskilled couples, implying that skilled couples agree in all of these cases (43).…”
Section: Discussionmentioning
confidence: 99%
“…Rahimi et al found that the distribution of roles, responsibilities, and power in skilled couples is fair while it is unfair in unskilled couples, implying that skilled couples agree in all of these cases (43).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the number of domestic and Iranian studies on marital and sexual problems of dual-career couples ( 4 – 5 ), it can be said that context and culture play an important role in how and causes of marital problems, especially sexual and marital problems of dual-career couples.…”
Section: Dear Editor-in-chiefmentioning
confidence: 99%